CPD AND DIGITAL TRANSFORMATION: HOW TECHNOLOGY IS REDEFINING TEACHER LEARNING - Ruzimurodova Nigora Oybek qizi (Modern American Journals, 2025)
In the digital era, Continuous Professional Development (CPD) has evolved from traditional training sessions into a dynamic, technology-driven process of lifelong learning. This article explores how digital transformation reshapes teacher learning by promoting collaboration, autonomy, and reflective practice. It highlights that technology enhances access to professional growth but must be grounded in meaningful pedagogy and emotional intelligence. The paper also examines challenges such as digital inequality, superficial engagement, and the need for institutional support to ensure that technological advancement strengthens, rather than replaces, the human essence of teaching.
Keywords: Continuous Professional Development, digital transformation, teacher learning, technology in education, reflective practice, collaboration, lifelong learning, emotional intelligence, professional growth.